2019
DOI: 10.24940/theijhss/2019/v7/i7/hs1907-072
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Internet Addiction among Seminarians in a Major Seminary in Kenya

Abstract: Prevalence of Internet Addiction among Seminarians in a Major Seminary in Kenya 1. Introduction Internet, a global system of telecommunications network is part of our daily lives and is being used everywhere in the world (Wallace, 2014). People use internet for various reasons: academic purposes, professional work, connecting to relatives and friends, online shopping and advertisement or leisure (Deursen & Dijk, 2009). Schools and universities use internet for teaching and learning. The more an institution use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The overall internet addiction gap between CUEA students and the seminarians is because CUEA participants were undergraduate students whereas the seminarians were both undergraduate and postgraduate students. In their study , Landry et. al., (2019) reported that postgraduate students emerged to be highly addicted to the internet at 41.7% level.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The overall internet addiction gap between CUEA students and the seminarians is because CUEA participants were undergraduate students whereas the seminarians were both undergraduate and postgraduate students. In their study , Landry et. al., (2019) reported that postgraduate students emerged to be highly addicted to the internet at 41.7% level.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence is within the range of 17 % -23% found by Xin, et. al., (2018) on a study conducted among youth study by Landry, Mbwayo & Ireri (2019) reported that the prevalence of internet addiction among seminarians in a major seminary in Kenya was 38.7%. The overall internet addiction gap between CUEA students and the seminarians is because CUEA participants were undergraduate students whereas the seminarians were both undergraduate and postgraduate students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the publications reviewed here, the main factors studied have resulted in personality (34 out of 40 studies), spirituality (Cahyono & Julom, 2015; Francis & Crea, 2019; Kosek, 2000; Mahalik & Lagan, 2001; Okozi, 2010; Sunardi, 2014) and intelligence (with IQs that turned out to be average, Banks et al, 1984; Gamino et al, 2007; Kuchan et al, 2013; Songy, 2007). Two studies assessed the perceived parental bonding of candidates (Cahyono & Julom, 2015; Sunardi, 2014), one emotional intelligence (Cahyono & Julom, 2015), while another study assessed gender-related conflict and stress (Mahalik & Lagan, 2001), one the quality of life (Prusak et al, 2021) and one (Landry et al, 2019) addiction (raising the question about the need for the seminary authorities to carry out random screening for internet addiction). Scholars also recommend the investigation of the candidate’s psychosexual integration (O’Donnell, 1997; Kleponis, 2016) and the use of pornography, particularly internet pornography (Kleponis, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Based on 20 selfreport items, the IAT assesses for the presence of addiction to the internet, electronic entertainment, social media, and general use of electronic devices, and also measures the severity of addiction, in terms of mild, moderate or severe and it takes about 5-10 min to be administered (Young, 2017). The study by Landry et al (2019) revealed that 4.6% of the seminarians examined with this tool had severe internet addiction, whereas 34.1% were moderately addicted, and that the seminarians are not always aware of their addiction.…”
Section: Iatmentioning
confidence: 99%